Lower dose and weekly schedules of selinexor in multiple myeloma - updated evidence on safety and efficacy - Baljevic, Muhamed; Schiller, Gary; Mark, Tomer M.; Van Domelen, Dane R.; Gasparetto, Cristina (Frontiers in Oncology, 2025)
BackgroundSelinexor, a first-in-class, oral exportin-1 inhibitor, showed activity in penta-refractory multiple myeloma (MM) in early trial exploration; however, the side-effect profile of twice-weekly dosing led to hesitant incorporation into widespread practice. Here, our objective is to provide updated clinical evidence highlighting the preserved efficacy and improved tolerability of once-weekly selinexor at lower doses in patients with previously treated MM compared to twice-weekly regimens.MethodsPatient-level data from the BOSTON, STOMP, STORM, and XPORT-MM-028 clinical trials were systematically evaluated to elucidate relationships between selinexor dosing schedule, regimen toxicities, and efficacy in patients with MM that had progressed after at least one prior therapy.ResultsUpdated results on once-weekly selinexor in combination with other anti-MM agents showed a reduced adverse event profile and improved tolerability compared with twice-weekly selinexor regimens, without compromise in efficacy. Furthermore, new data from several regimens with weekly selinexor delivery suggest that patients who had selinexor dose reductions or were treated in cohorts with a lower selinexor starting dose had reduced rates of adverse events, and superior durations of response. Weekly selinexor in combination with pomalidomide or carfilzomib in particular showed efficacy in difficult-to-treat, multiclass relapsed/refractory MM, including MM refractory to prior BCMA-directed therapies.ConclusionsIn a rapidly evolving field of previously treated MM, lowering of selinexor dose and frequency into weekly regimens showed a more feasible and tolerable treatment with continued efficacy when compared to twice-weekly schedules, paving the path for effective management of multiclass refractory MM, including patients with very advanced disease.